Hypoglycemic effect of banana peel extract (Musa Paradisiaca Var Kepok) in New Zealand White Diabetes Hyperlipidemia - Samiasih, Amin; Subagio, Hertanto Wahyu; Dharmana, Edi; Susanto, Hardono (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Introduction: banana peels just end up in the trash to date. It needs to be thought of waste processing into a more useful product for health. This study aims to determine the effect of peel extract (Musa Paradisiaca var. kapok) toward the blood sugar level of New Zealand White (NZW) rabbits which have diabetes hyperlipidemia. Method: 27 male New Zealand White rabbit, age 4 months, average weight 1.5-2 kg. The raw materials of the ethanol extract were Musa Paradisiaca Var Kepok peels that were obtained from Traditional Market, Demak, Central Java Indonesia. Type of experimental laboratory research was conducted with a randomized control design pre-posttest design. The 104-day study was conducted at LPPT unit 4 UGM that has been standardized internationally. Results: The test results of repeated ANOVA on the blood sugar group 1 (O1) shows that at least 2 measurement times that had significantly different mean values with p-value= 0.003 <0.05. The result of the Friedman test on the blood sugar level for group 2 (O2) showed that at least 2 measurement times having mean value was significantly different with p-value= 0.001 <0.05. The group 3 (O3) indicated that at least 2 measurement times had significantly different value mean with p-value= 0.045 <0.05. There are the differences on blood sugar levels in each group and at each measurement time. Administration of ethanol extract of musa paradisiaca var kepok peels in the group (O1) with dose 200mg / kg bb and dose of 400mg / kg bb in group 2 (O2) have the same effect of hypoglycemia. Conclusion: an ethanol extract of musa paradisiaca var kepok peels have a hypoglycemia effect on New Zealand White rabbit with Diabetic Hyperlipidemia.